2021
DOI: 10.3390/ijms222413497
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Kynurenine and NAD+ Salvage Pathways during the Successful Treatment of Inflammatory Bowel Disease Suggest HCAR3 and NNMT as Potential Drug Targets

Abstract: A meta-analysis of publicly available transcriptomic datasets was performed to identify metabolic pathways profoundly implicated in the progression and treatment of inflammatory bowel disease (IBD). The analysis revealed that genes involved in tryptophan (Trp) metabolism are upregulated in Crohn’s disease (CD) and ulcerative colitis (UC) and return to baseline after successful treatment with infliximab. Microarray and mRNAseq profiles from multiple experiments confirmed that enzymes responsible for Trp degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 67 publications
(86 reference statements)
3
24
0
Order By: Relevance
“…In further studies, pathways affected during IBD progression and post treatment recovery included genes involved in tryptophan degradation, receptors of tryptophan metabolites and NAD + turnover (i.e., IDO, KYNU, HCAR3, CD38 and NNMT) being synchronously co-regulated [ 61 ]. Treatment with Infliximab (TNFα inhibitor) removes excess of inhibitory NAM and helps maintain high levels of NAD + -dependent pro-inflammatory signaling [ 62 , 63 ]. While KYNU relevance to inflammation has been demonstrated in psoriasis in which epithelial cells only expressed KYNU after stimulation with IFNγ or TNFα; and combining the cytokines significantly enhanced IDO and KYNU in various cell types as much as 100 fold [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In further studies, pathways affected during IBD progression and post treatment recovery included genes involved in tryptophan degradation, receptors of tryptophan metabolites and NAD + turnover (i.e., IDO, KYNU, HCAR3, CD38 and NNMT) being synchronously co-regulated [ 61 ]. Treatment with Infliximab (TNFα inhibitor) removes excess of inhibitory NAM and helps maintain high levels of NAD + -dependent pro-inflammatory signaling [ 62 , 63 ]. While KYNU relevance to inflammation has been demonstrated in psoriasis in which epithelial cells only expressed KYNU after stimulation with IFNγ or TNFα; and combining the cytokines significantly enhanced IDO and KYNU in various cell types as much as 100 fold [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCAR3 and LRRC18 were also sensitive to exposure to high altitudes and might be able to predict whether a person would develop HAPC. HCAR3 activates Gi signaling in immune cells and is also a therapeutic target for breast cancer and inflammatory bowel diseases [ 40 , 41 , 42 ], and these diseases cause hypoxia response. HCAR3 activates ERK1/2, which in turn activates NFκB-mediated hypoxia responses.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 957 DEGs were screened: 478 up regulated genes and 479 down regulated genes. Lee et al [41], Gijsbers et al [42], Hashash et al [43], Wnorowski et al [44] and Kyodo et al [45] found that FCGR3A, CXCL8, MUC1, HCAR3 and DUOX2 might play an important role in the pathophysiology of CD. Nourse et al [46] and Nakashima et al [47] found that FCGR3A and MUC1 was altered expressed in coagulation and fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%